The Alstroemeriaceae in Peru and neighbouring areas - Hofreiter, Anton (2006)
The family Alstroemeriaceae with special emphasis in Peru is revised using morphological and distributional data. Species in this family were reinvestigated on the basis of all types, material housed in several herbaria and five field trips, each of which lasted several weeks, were undertaken to South America to study the plants in the field. The taxonomic and collection history of the genus is described and for each species the typical growth forms and their variability, habitat preferences and general distribution are discussed. A key to determine the species of Peru in English and Spanish is provided. The study area comprise five geographic units recognised: Amotape-Huancabamba-region (Ecuador, Peru), Cordillera Occidental (Peru), Cordillera Central (Peru), Cordillera Oriental (Bolivia, Peru) and the Altiplano (Bolivia, Peru). The family as here circumscribed comprises two species of Alstroemeria and 68 species of Bomarea, of these 68 species 43 species are members of subgenus Bomarea, 9 species of subgenus Sphaerine and 16 of the subgenus Wichuraea. The fourth and last subgenus into Bomarea genus denominated Baccata cannot be found in the area of this study. Six new species to science of Bomarea are described: B. amazonica, B. libertadensis, B. lopezii, B. macusanii, B. pseudopurpurea, B. weigendii.